PEMBERDAYAAN KELUARGA UNTUK SADAR HIPERTENSI MELALUI PELATIHAN AKUPRESUR DAN RELAKSASI OTOT PROGRESIF - Silvanasari, Irwina Angelia (P3M Universitas Aisyiyah Surakarta, 2025)
Hypertension is a common disease not only in the older age group but also in the productive age group. Various health problems will arise if the hypertension that occurs cannot be controlled properly. Controlling hypertension requires high awareness and adequate skills in self-care management. A family approach needs to be taken to provide more optimal results. Empowering families who are aware of hypertension through acupressure and progressive muscle relaxation carried out in this activity can increase family knowledge and skills in controlling hypertension. The family has a good understanding of hypertension and is able to practice acupressure and progressive muscle relaxation well. Families can teach and accompany family members who suffer from hypertension regarding controlling their hypertension in their daily lives on a regular basis. It is hoped that good understanding and ability to control hypertension can improve health status and improve the quality of life for families with hypertension sufferers.